Prevalence Pattern of Adverse Drug Reaction with Causality Assessment to Chemotherapy in a Tertiary Hospital, Nepal: - Shah, Rekha; Gupta, Prem Kumar; Sapkota, Sulav; Rai, Prakash (Birat Journal of Health Sciences, 2025)
Introduction: The low therapeutic window and high toxicity of Chemotherapeutic agents make adverse drug reactions (ADRs) a major worry in cancer treatment. The occurrence, cause, and severity of adverse medication reactions related to chemotherapy in a tertiary were aim to be investigated in this study.Objectives: To find out the prevalence pattern and causality outcome of ADRs to chemotherapeutic agents in Birat Medical College Teaching Hospital.Methodology: A hospital-based, Observational cross-sectional study was conducted among 200 cancer patients under systemic anticancer medication (SACT) at Birat Medical College Teaching Hospital from May to October 2024. The Naranjo's Causality Assessment Scale was used to assess causality; severity was measured using the Hartwig and Siegel Assessment Scale.Results: Among the 200 participants, the mean age was 55.05 ± 14.11 years; breast cancer 44(22%) was the most prevalent malignancy. Reported Anorexia 28(14%) and taste changes 22(11%) were the ADRs. Causality evaluation found most ADRs as possible or likely; definite. Most reactions were of mild to moderate severity, however, severe ADRs were observed including dyspnea, infection, and mucositis. Statistically significant association between age category and in causality of ADRs (p=0.039)Conclusions: Chemo-related ADRs are quite frequent; they include moderate-to-mild gastrointestinal symptoms. The notable age-ADR link calls for increased monitoring for elderly patients, thereby highlighting the strengthening and boosting local pharmacovigilance in Nepal.